56.1: Invited Paper: A Holographic Waveguide Display with Polarization Volume Gratings. (24th February 2021) - Zhang, Yuning; Cui, Jingyi; Weng, Yishi
Abstract : We report a polarization sensitive volume grating in this paper. In addition, a double‐layer waveguide using this kind of grating as coupling elements has been demonstrated to realize a full‐color near‐eye display. The results show that about 85% diffraction efficiency covering all of the red, green and blue spectra with a diagonal FOV of around 35° is obtained for the proposed waveguide prototype.